Effects of a short-term removal of the dominant male on vocalization in captive groups of large-billed crows (Corvus macrorynchos) - Illia Aota; Mayu Takano; Ei-Ichi Izawa (Royal Society Open Science)
Dominance hierarchy is widespread among group-living animals as a conflict resolution strategy to avoid the cost and risk of fights among individuals. Dominance signals are well-known mechanisms that allow individuals to assess their opponent’s fighting ability without physical contact, thereby maintaining dominance relationships. In fission–fusion societies, where group composition is fluid, dominance status can shift depending on the current group members. In such situations, vocal signals may be particularly useful as dominance signals due to their easy modification by the signaller. In this study, we investigated the relationship between rank-dependent behaviours and rank ascending by temporarily removing individuals from captive groups of large-billed crows (Corvus macrorhynchos). We removed either the first-ranked or third-ranked individuals from the group for 1 day and compared the behaviours of the remaining group members before the removal, during the removal and after the removed individuals rejoined the group. We found that the number of sequential ka calls, which is assumed to be a status signal, increased only during the removal of first-ranked individuals and decreased after they rejoined the group. These results suggest that sequential ka calls serve as dominance signals, and the subordinates flexibly adjust their vocalization depending on the presence of high-ranked individuals.